A brave new world: the new normal for general practice after the COVID-19 pandemic. Issue 3 (August 2020) - Khan, Nada; Jones, Daniel; Grice, Adam; Alderson, Sarah; Bradley, Stephen; Carder, Paul; Drinkwater, Jessica; Edwards, Helen; Essang, Blessing; Richards, Suzanne; Neal, Richard
No abstract available